Tracer-free fuel-air ratio measurements & thermodynamic phase determination in diesel sprays by Raman spectroscopy - Klima, Tobias C.; Peter, Andreas; Wensing, Michael; Braeuer, Andreas Siegfried (ICLASS 2018 - 14th International Conference on Liquid Atomization and Spray Systems, 2018)
Raman spectroscopy is applied in spray injection measurements at diesel-relevant conditions for fuel-air ratio determination and a novel evaluation technique sheds light on the phase transition progress in the spray. The measurement approach is explained in detail for both fuel-air measurements and liquid fraction measurements. Data on fuel-air ratio is gained without the use of tracers along a one-dimensional section of the spray, reliably quantified by calibration of the setup at the relevant conditions. Single-shot and mean data of the fuel-air ratio are shown and discussed. The liquid fraction of the fuel is analyzed and the influence of ambient parameters shown. The behavior of the liquid fraction along the section in the spray shows the influence of ambient pressure and temperature on phase transition, yielding new information about the distribution of liquid and gaseous fuel with respect to the total fuel fraction. Conventional techniques for the visualization of the liquid phase like e.g. Mie-scattering are limited with respect to image resolution and rely on detection of refractive index gradients, a diffuse premise at potentially transcritical conditions. The introduced approach provides below-pixel resolution of information on fuel phase and fuel-air ratio and does not rely on possibly misleading requirements like phase boundaries., thus overcoming the mentioned limitations.
Keywords: Optical measurement; Phase transition; Raman; Spray; Supercritical; Transcritical